Chip design for thin-film deep ultraviolet LEDs fabricated by laser lift-off of the sapphire substrate. (3rd November 2017) - Cho, H K; Krüger, O; Külberg, A; Rass, J; Zeimer, U; Kolbe, T; Knauer, A; Einfeldt, S; Weyers, M; Kneissl, M
Abstract: We report on a chip design which allows the laser lift-off (LLO) of the sapphire substrate sustaining the epitaxial film of flip-chip mounted deep ultraviolet light emitting diodes. A nanosecond pulsed excimer laser with a wavelength of 248 nm was used for the LLO. A mechanically stable chip design was found to be the key to prevent crack formation in the epitaxial layers and material chipping during the LLO process. Stabilization was achieved by introducing a Ti/Au leveling layer that mechanically supports the fragile epitaxial film. The electrical and optical characterization of devices before and after the LLO process shows that the device performance did not degrade by the LLO.